Development and evaluation of a ceramic diffusive layer based DGT technique for measuring organic micropollutants in seawaters. (November 2021) - Xie, Huaijun; Dong, Yingchao; Chen, Jingwen; Wang, Xueling; Fu, Mao
Highlights: A novel DGT technique coupled with a ceramic diffusive layer was developed. The ceramic membrane exhibited adsorption inertness to organic micropollutants. The developed DGT technique was less affected by flow rate of solution. Abstract: Diffusive gradients in thin-films (DGT) technique has been well demonstrated as a robust tool for measuring organic micropollutants (OMPs) in the aquatic environment. However, potential adsorption of the OMPs on organic polymer filters and flow rate of waters can affect the measuring results of the DGT method, hence tedious work should be conducted to reduce these interferences. In the present study, a novel DGT technique coupled with a ceramic diffusive layer was developed to measure the OMPs in seawaters. The ceramic diffusive layer exhibited adsorption inertness to the OMPs with various log K ow values. Moreover, the ceramic diffusive layer based DGT technique was proved to be less affected by the flow rate than the traditional DGT with agarose diffusive layer. The developed DGT device exhibited kinetic accumulation for the targets during a 6-d deployment, and measurement of the OMPs by the DGT method was independent with pH and ionic strength. Finally, the developed DGT sampler was applied in coastal waters of Dalian, and eight OMPs were detected with levels ranging from 1.58 to 13.1 ng/L. The development of the ceramic diffusive membrane can lead to simplification of the DGT applications, promoting the progress of the OMPs monitoring technology.